EFFECT OF KAOLIN ON BIOCHEMICAL PARAMETERS AGAINST AEROMONAS HYDROPHILA IN CYPRINUS CARPIO - Muthana N. Al-Ghazaly; A. J. Al-Rudainy (The Iraqi Journal of Agricultural science, 2024)
The present study aimed to evaluate the role of kaolin on hematological and biochemical profiles of common carp, Cyprinus carpio infected with Aeromonas hydrophila, A total of 180 of common carp were collected 40 g ; 60 fish were used to determine the median lethal dose LD50 of A. hydrophila, )LD50 was 1.57 × 106 CFU/ml) for 15 days.  120 fish were randomly distributed into six treatment groups (10 fish/treatment in duplicate) as follows:  C- served as control negative group (without infection and treatment); C+ act as control positive group (infected with A. hydrophila but not treatment with Kaolin); T1, T2, T3 and T4 were intraperitoneally (IP) injected with A, hydrophila   (at dose of 0.1 ml) and then treated with Kaolin at concentrations of 2, 4, 6 and 8 g/L respectively.  In hematological indices, the experimental groups of carp (C+, T1, T2, T3 and T4) showed a significant (P<0.01) decrease in the number of erythrocytes, Hb content and PCV% compared to C- group. While, WBC numbers showed a significant (P<0.01) increase in all experimental carp groups relative to the C- group. As far as biochemical profile are concerned, the experimental groups of carp (C+, T2, T3 and T4) reported a significant (P<0.05) increase in total protein compared to C- group. In Globulin, Groups (T2, T3 and T4) showed a significant (P<0.01) increase compared to C- group. In conclusion, the treatment of common carp with Kaolin particularly at concentration of 8 g/L (T4) reduced the effect of A. hydrophila.